MULTIFOCAL/MULTICENTRIC BREAST CANCER: HISTOLOGICAL STRUCTURE OF TUMOR - Munira Kh. Norbekova ,; Farrux Sh. Fayziyev , (Central Asian Journal of Medicine, 2025)
Aim: This study aims to analyze the histological and molecular biological characteristics of large and small tumors in multifocal and multicentric breast cancer (BC) patients. Materials and methods: Data from 133 patients treated at the Republican Specialized Oncology and Radiology Scientific Practical Center and its branches between 2018 and 2023 were retrospectively analyzed. Results: Results revealed no significant statistical difference in the age of patients among the groups (p = 0.324). However, significant differences were observed in lymph node involvement (p = 0.001), histological grade (p = 0.02), histological type (p = 0.03), and type of surgery (p = 0.001). The study showed that multifocal and multicentric tumors are biologically more aggressive than unifocal tumors, with a higher tendency to metastasize and poorer prognosis. Conclusion: The results of the study confirmed that the characteristics of multifocal breast cancer can be a necessary criterion for predicting the outcome of the disease.